2020
DOI: 10.21203/rs.3.rs-16302/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Live Poultry Market Closure and Avian Influenza A (H7N9) infection in cities of China, 2013-2017: An ecological study

Abstract: Background Previous studies have proven that the closure of live poultry markets (LPMs) was an effective intervention to reduce human risk of avian influenza A (H7N9) infection, but evidence is limited on the impact of scale and duration of LPMs closure on the transmission of H7N9. Method Five cities (i.e., Shanghai, Suzhou, Shenzhen, Guangzhou and Hangzhou) with the largest number of H7N9 cases in mainland China from 2013-2017 were selected in this study. Data on laboratory-confirmed H7N9 human cases in those… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
1
1
Order By: Relevance
“…In the past, it was generally closed for shorter periods of about 2 weeks. The results of our and previous studies 11 show that no matter whether it is a shortterm or long-term market closure, the effect on controlling the spread of AIV among live birds is not clear. However, from the perspective of human-to-human transmission of the AIV, in areas where the virus is found in live poultry or people, the rapid implementation of LPM closures has a relatively good control effect in the short term.…”
Section: Discussioncontrasting
confidence: 82%
“…In the past, it was generally closed for shorter periods of about 2 weeks. The results of our and previous studies 11 show that no matter whether it is a shortterm or long-term market closure, the effect on controlling the spread of AIV among live birds is not clear. However, from the perspective of human-to-human transmission of the AIV, in areas where the virus is found in live poultry or people, the rapid implementation of LPM closures has a relatively good control effect in the short term.…”
Section: Discussioncontrasting
confidence: 82%
“…This study further confirmed that Guangxi, with a considerable amount of live broiler movements, faces substantial challenges in AI risk management. The findings indicate that the live broiler trade volume was still large and very active in southern China, despite the closure of LBMs since late 2016 in response to the dramatic increase of human infections with H7N9 (China News Service, 2017; Chen et al, 2020). The study findings further confirmed earlier observations that public consumption demand for live poultry remained high even during the H7N9 epidemics (Lin et al., 2017).…”
Section: Discussionmentioning
confidence: 99%